Radio emission towards Eta Carinae - Rästas, Margit (My University, 2011)
Eta Carinae with its peculiar surrounding has been a mystery for decades despite numerous surveys carried out. In this paper we focus on a H26α emission line in order to find out if the results will shed some light on the subject. In order to have a clearer picture of Eta Carinae the earlier work published on the studies of the object has been summarized in the introduction. Before going deeper into the studies some theories are explained that are essential to understand the analysis done in the second part of the paper. The theories include local thermodynamic equilibrium (LTE) conditions applied to the medium in order to determine the line-to-continuum intensity ratio which yields an estimate of electron temperature of the emitting region. This value is necessary for the subsequent model calculations. The departures from LTE are also relevant to understand and have been discussed in separate section. For the analysis we have assumed the emission to originate from ionized wind and therefore a simplified spherically symmetric wind model with uniform mass loss rate has been described as well as applied. It is clear that the actual structure of the wind may strongly deviate from the model though. The spectral energy distribution (SED) of Eta Carinae discussed in the section describes the origin of the continuum emission. Since the analyzed line profile is showing broadening effect in the wings another section is dedicated to a possible broadening theory - Stark effect. Some rather interesting results from earlier studies on some recombination lines towards Eta Carinae claiming a maser emission have been discussed in a separate section. In the final section we give the description of data and its analysis with MATLAB. First we notice that the He/H ratio is out of the ordinary. When concentrating on H26α line we try to see the similarities/discrepancies between the observed line profile and the profile we obtain by using the simple wind model. The terminal velocity of the wind has been estimated in different ways resulting in differences in line profiles expected from the simple model of wind in LTE. All of those however are surprisingly low for such a massive star. To account for the line wing broadening the impact broadening effect is applied to the modeled profile which for one specific modified case gives a rather good fit. Since there has been an abrupt change over a short period of time observed in the line intensities lately we have also tried to estimate the timescale for the recombination.
Keywords: Astronomi, astrofysik och kosmologi; Grundläggande vetenskaper; Astronomy, Astrophysics and Cosmology; Basic Sciences